Empowering tomorrow’s public health researchers and clinicians to develop digital health interventions using chatbots, virtual reality, and other AI technologies - W. Scott Comulada; W. Scott Comulada; Catherine McQueen; Cathy M. Lang (Frontiers in Public Health, 2025)
BackgroundArtificial Intelligence (AI)-based digital health interventions incorporating technologies like chatbots and augmented/virtual reality are reshaping the healthcare delivery landscape. The rollout of these technologies warrants updated graduate curricula to train future healthcare professionals. In response, the authors incorporated additional topics relevant to digital health intervention development into a graduate-level digital health communication course and evaluated student feedback.MethodsThe authors developed four lectures on two−/one-way digital health messaging strategies, AI/large language models, chatbots, and augmented/virtual reality, and a chatbot development tutorial as a lab. They evaluated students’ perceptions of the course and the benefits of the new content after course completion through standard and supplemental course evaluations.ResultsEleven of 16 enrolled students completed the course evaluation, and 8 completed the supplemental survey. Most students were from the school of public health and reported female gender. One of 8 students completing the survey reported prior experience creating chatbot and AR/VR content. The overall average course rating was high (7.45 out of 9). Open-ended survey responses about the new content were mixed with enthusiasm and questions about its relevance over content on traditional communication modalities in preparation for public health work.ConclusionStudent feedback underscored course content value, along with guidance to better emphasize how chatbots and augmented/virtual reality are relevant to clinical and public health practices. More applications relevant for diverse populations could elucidate the value of new technologies for students who will develop digital-based interventions. Applications focusing on commonalities could also solidify students’ understanding of intervention development principles that will remain, as technologies evolve.